Introduce Ce3+ Ions to Realize Enhancement of C+L Band Luminescence of KMnF3: Yb, Er Nanoparticles - Hao Cui; Daguang Li; Yu Yang; Yuewu Fu; Yanhui Dong; Jing Yin; Weiping Qin; Zhixu Jia; Dan Zhao (Nanomaterials, 2023)
Polymer-based waveguide amplifiers are essential components in integrated optical systems, as their gain bandwidths directly determine the operating wavelength of optical circuits. However, development of the wideband gain media has been challenging, making it difficult to fabricate devices with broadband amplification capability. Rare earth ion-doped nanoparticles (NPs) are a key component in the gain media, and their full width at half maximum (FWHM) of the emission peak decides the final gain bandwidth of the gain media. Here, KMnF3: Yb, Er, Ce@KMnF3: Yb NPs with the broad full width at half maximum (FWHM) of the emission peak covering the S+C band was prepared. The NPs were synthesized using a hydrothermal method, and the FWHM of the emission peak of NPs reached 76 nm under the excitation of a 980 nm laser. The introduction of Ce3+ ions and a core-shell structure coating greatly enhanced the emission intensity of NPs at C band. Since KMnF3: Yb, Er, Ce@KMnF3: Yb NPs have exceptional broadband luminescence properties at C band, KMnF3: Yb, Er, Ce@KMnF3: Yb NPs can be the potential gain medium in the future polymer-based waveguide amplifiers.